Evaluasi Kinerja Seismik Rangka Beton Pemikul Momen Khusus dengan PERFORM-3D - Utomo, Junaedi; Ekaputri, Januarti Jaya; Antonius, Antonius; Lie, Han Ay (MEDIA KOMUNIKASI TEKNIK SIPIL, 2019)
Seismic performance of reinforced concrete frame Buildings which have been designed as Special Moment Resisting Frames in accordance to three Indonesian codes (SNI 1727-2013, SNI 1726-2012 and SNI 2847-2013) can be evaluated using nonlinear dynamic analysis. Criteria related to strength such as component plastic rotation capacity, lateral displacement as well as criteria related to damage of elements in the structures were used to evaluate the seismic performance of the buildings. Assessment to the moment and curvature capacities of the cross sections of beams and columns were done using XTRACT. The global seismic performance of the structures depends on the seismic performance of components in the structures. In nonlinear model of the structures, the degrading strength of the components were modeled to take into account the gradual reduction of the contributed components to the resistance of the structures. PERFORM-3D is one of the software that can be used to generate nonlinear model of structures. Seismic performance level of structures can be obtained from the results of the nonlinear dynamic analysis using PERFORM-3D. The Seismic performance level can be utilized for: (1) detecting any weaker part in the structures, and (2) evaluating the improved design of the structures for enhancing the seismic performance of structures.